EMPLOYEE PERFORMANCE REVIEWING FROM DISCIPLINE, MOTIVATION, WORK ENVIRONMENT, AND LEADERSHIP IN PUBLIC WORKS AND SPATIAL PLANNING OFFICES KLATEN DISTRICT - Tri Wahyu Joko Nugroho; Istiatin Istiatin; Bambang Mursito (PERCIPIENCE International Journal of Social, Administration, & Entrepreneurship, 2022)
This study aims to determine the effect of simultaneously (simultaneously) or partially the variables of discipline, motivation, work environment and leadership on employee performance at the Public Works and Spatial Planning Office of Klaten Regency.This research method uses a quantitative descriptive research design. The population in all employees who work in the Department of Public Works and Spatial Planning Klaten Regency, amounting to 291 people. The sampling technique used in this study is a purposive sampling technique with a total sample of 81 respondents. Collecting data by using a questionnaire. The data analysis technique used is statistical analysis, namely multiple linear regression test, F test, t test, and the coefficient of determination. The results of the study indicate that discipline, motivation, work environment and leadership partially and significantly affect the performance of employees at the Department of Public Works and Spatial Planning, Klaten Regency. Suggestions from this research, employees of the Klaten Regency Public Works and Spatial Planning Office continue to improve discipline, motivation, work environment and existing leadership, so that employee performance will increase and be better than before.